The protection of movable cultural property in wartime: Pre-conflict planning in Sweden. Issue 3 (August 2022) - Legnér, Mattias
Abstract: Modern warfare has prompted states to protect collections of cultural property by evacuating them to safe locations at times of war. Building on previously classified documents in archives, inquiries and other sources, this article investigates how planning for such evacuation was carried out in Sweden from 1939 to the 1990s. After the end of the Cold War, existing evacuation plans were finally scrapped. Due to the worsening security situation in the region, Swedish heritage institutions today need to build preparedness anew. It is shown that the evacuation of large volumes of property out of cities for practical reasons never was a realistic scenario, but probably should be restricted to a minimum of carefully selected objects, records and books. The process of selecting, transporting, finding safe locations to take the property to, and determining how to monitor it needs to be carefully planned during peaceful conditions in order to efficiently safeguard the collections in wartime. The relationship between Swedish planning and the 1954 Hague Convention, and how other states can learn from this study, is finally discussed.